2007
DOI: 10.1177/1557988307299477
|View full text |Cite
|
Sign up to set email alerts
|

Men's Tobacco and Alcohol Use During and After Pregnancy

Abstract: Men's health risk behaviors are rarely considered as a component of their partners' prenatal care. Men living with a pregnant partner completed telephone surveys at two time points, during pregnancy and postpartum, answering questions about tobacco and alcohol use behaviors and other sociodemographic variables. Men's smoking did not change significantly from pregnancy (46.9%) to postpartum (45.8%). Hazardous drinking (five or more drinks/day in a month) changed from 27.1% to 22.9%. Nonsmoking status of men was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 35 publications
(44 reference statements)
2
28
0
Order By: Relevance
“…An extensive body of literature, mostly from English-speaking countries, demonstrates that married or cohabiting partners tend to have similar substance use patterns, problem drinking, and alcohol use disorders . In expectant parents, a few prior studies reported positive associations between partners' levels of smoking and their levels of alcohol consumption (Everett et al, 2005(Everett et al, , 2007Waterson et al, 1990). …”
Section: Discussionmentioning
confidence: 99%
“…An extensive body of literature, mostly from English-speaking countries, demonstrates that married or cohabiting partners tend to have similar substance use patterns, problem drinking, and alcohol use disorders . In expectant parents, a few prior studies reported positive associations between partners' levels of smoking and their levels of alcohol consumption (Everett et al, 2005(Everett et al, , 2007Waterson et al, 1990). …”
Section: Discussionmentioning
confidence: 99%
“…Limited data suggests that substance use among expectant fathers is positively correlated with both substance use among their pregnant partner and relapse of substance use postpartum. [30-33] Partners within a relationship tend to display similar patterns of substance use and partner's cessation of substance use is a strong predictor of one's own cessation of substance use. [34, 35] However, there exists a limited understanding of alcohol use among expectant fathers and no studies have investigated this area of study among South African men with pregnant partners.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of this study that the smokers believed in willpower as the key for successful quit symbolizes masculine norms of strength and self-control for men in all cultures (Everett et al, 2007;Oliffe et al, 2012;White et al, 2012a). However, the cynicism the Chinese men showed to Canadian men's help-seeking behavior sheds light on important variations in the way masculinities are practiced in different cultures.…”
Section: Discussionmentioning
confidence: 87%
“…Men's smoking is universally associated with gender expectations for men, signifying masculine ideals of independence, physical resilience to harmful substances, and capacity to endure risk taking (Everett et al, 2007;Oliffe et al, 2012;White, Oliffe, & Bottorff, 2012a). Masculinities are multidimensional, contested, and dynamic.…”
Section: Introductionmentioning
confidence: 97%